ANALISIS POTENSI WISATA SEJARAH DAN BUDAYA UNTUK PENGEMBANGAN PARIWISATA BERBASIS KEARIFAN LOKAL DI NAGARI SITUJUAH BATUA - Najmi, Najmi; Novio, Rery; Hastuti, Hera; Yefterson, Ridho Bayu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Nagari Situjuah Batua, located in Situjuah Limo Nagari District, 50 Kota Regency, is a village that has a history that is quite different from other villages in West Sumatra. The history of this village is a major event and is always remembered by the people of Situjuah Batua itself. The event was the Situjuah Event. This event is always commemorated by the community every January 15. This event is a historical event that occurred during the Physical Revolution when the Indonesian Government maintained its independence from Dutch colonialism. The Situjuah incident can be said to be an event that paved the way for the Minangkabau people, especially the people in Nagari Situjuah Batua related to the betrayal committed by their own nation and the killing of heroes by the Dutch army. The commemoration of the event is not just an ordinary commemoration but also coincides with the